'EU-on-demand': developing national qualifications frameworks in a multi-level context. (November 2016) - Elken, Mari
The development of comprehensive national qualifications frameworks (NQFs) across Europe has been sparked by the introduction of the European Qualifications Framework (EQF) in 2008. Taking an institutional perspective, this article examines the development of NQFs in three countries, in light of developments that have taken place at the European level. The three cases (Estonia, Ireland, Norway) show how these processes are highly dependent on the links to the European level, the sequence of the process, how the European initiative is coupled to national issues, actor involvement locally and the time available. The article shows the potentially problematic nature of introducing European solutions on a national level as agenda-setting processes can become omitted and ad hoc linkages to national policy domains can be weakly developed.